2020
DOI: 10.2217/mmt-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study Of Talimogene Laherparepvec Use in the Anti-PD-1 era for Melanoma in the US (COSMUS-2)

Abstract: Aim: Talimogene laherparepvec (T-VEC) is an intralesional therapy for unresectable, metastatic melanoma. T-VEC real-world use in the context of anti-PD1-based therapy requires further characterization. Materials & methods: A retrospective review of T-VEC use from 1 January 2017 and 31 March 2018 for melanoma patients was conducted at seven US institutions. Results: Among 83 patients, three categories of T-VEC and anti-PD-1 therapy were identified: T-VEC used without anti-PD-1 (n = 29, 35%), T-VEC after ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Because several other promising agents were available, many patients were considered for T-VEC only after having progressive disease after other treatments. Over the last 5 years, however, there has been considerable real-world data published providing a better idea of how best to integrate T-VEC treatment into the clinical practice and how to optimize patient selection and management ( Perez et al, 2018 ; Louie et al, 2019 ; Mohr et al, 2019 ; Perez et al, 2019 ; Louie et al, 2020 ; Sun et al, 2020 ; Kleemann et al, 2021 ; van Akkooi et al, 2021 ). In addition, techniques for injecting T-VEC have now been well established ( Figure 1 ).…”
Section: Real World Experience With T-vecmentioning
confidence: 99%
See 1 more Smart Citation
“…Because several other promising agents were available, many patients were considered for T-VEC only after having progressive disease after other treatments. Over the last 5 years, however, there has been considerable real-world data published providing a better idea of how best to integrate T-VEC treatment into the clinical practice and how to optimize patient selection and management ( Perez et al, 2018 ; Louie et al, 2019 ; Mohr et al, 2019 ; Perez et al, 2019 ; Louie et al, 2020 ; Sun et al, 2020 ; Kleemann et al, 2021 ; van Akkooi et al, 2021 ). In addition, techniques for injecting T-VEC have now been well established ( Figure 1 ).…”
Section: Real World Experience With T-vecmentioning
confidence: 99%
“…The authors concluded that with more clinical experience after 2017, patients were appropriately kept on treatment longer as more physicians recognized the possibility of pseudo-progression following T-VEC treatment. Another trial reported for patients in the 2017–2018 era evaluated the relationship between T-VEC and anti-PD-1 treatment ( Sun et al, 2020 ). In 83 patients from multiple institutions, three patterns were observed.…”
Section: Real World Experience With T-vecmentioning
confidence: 99%
“… 38 Instead, side effects are generally mild and arise from an anti-inflammatory response, causing fatigue, mild flu-like symptoms and/or arthralgias, 1 and/or local irritation or lesion ulceration. 32 , 39 …”
Section: Intratumoral Strategiesmentioning
confidence: 99%